2012
DOI: 10.1159/000343232
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Ileal Carcinoids

Abstract: Identification of common molecular mechanisms is needed to facilitate the development of new treatment options for patients with ileal carcinoids. Purpose of Review: Recent profiling studies on ileal carcinoids were examined to obtain a comprehensive view of risk factors, genetic aberrations, and transcriptional alterations. Special attention was paid to mechanisms that could provide novel targets for therapy. Results: Genome-wide association studies have shown that single nucleotide polymorphisms (SNPs) at IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 243 publications
3
10
0
Order By: Relevance
“…Since the SI-NETs examined in this study were positive for TPH1, Tac1, NeuroD1 and ChgA and negative for GCG or NTS , the results support the generally accepted proposal that the SI-NET originates from a group of serotonin and substance P producing EC cells 1-4 . Our interest was to estimate if this cell of origin belongs to the ISC gene-expressing subset.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Since the SI-NETs examined in this study were positive for TPH1, Tac1, NeuroD1 and ChgA and negative for GCG or NTS , the results support the generally accepted proposal that the SI-NET originates from a group of serotonin and substance P producing EC cells 1-4 . Our interest was to estimate if this cell of origin belongs to the ISC gene-expressing subset.…”
Section: Discussionsupporting
confidence: 88%
“…Although rare, SI-NETs are the most common malignant tumors of the small intestine 1 . They display unique biological and genetic profiles that may account for their malignant characteristics and are distinct from other endocrine tumors 1, 2 . Although SI-NETs are thought to originate from enterochromaffin (EC) cells 3, 4 , their precise origin and development remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the MYO5B mutations identified in this study could be found in the online MVID mutation database (http://mvid-central.org, June 25, 2015). Furthermore, MYO5B is positioned at chromosome arm 18q21.1, where chromosomal imbalances have been reported in NETs . Additional mutations in other myosin family members were identified in the current study ( e.g., MYO5A ) and are also reported in other PCC/PGL sequencing studies ( e.g.…”
Section: Discussionsupporting
confidence: 82%
“…The function of GPR56 in different cancer types was found to differ, with both pro- and anti-tumorigenic properties, so the therapeutic implication of targeting GPR56 in cancer in general awaits careful evaluation. ADGRG4 (GPR112) was reported to serve as a marker for neuroendocrine carcinoma cells [151] and proposed a therapeutic target for treating ileal carcinoids [50]. …”
Section: Tumor Therapy and Adhesion Gpcrsmentioning
confidence: 99%